Foreign Worker Employment Violations in Majalengka: A Legal Analysis Based on Law No. 13 of 2003 - Herry Farhan Syafiq (Rechtsvinding, 2026)
This study analyzes violations in the employment of foreign workers (TKA) in Majalengka Regency under Law Number 13 of 2003 on Manpower and its implementing regulations, including Government Regulation Number 34 of 2021 and Minister of Manpower Regulation Number 8 of 2021. Majalengka offers a distinctive case due to rapid industrial growth and rising foreign labor utilization, which heighten local regulatory and supervisory challenges. The research uses a normative legal method with statutory and conceptual approaches, supported by qualitative analysis to identify common violation patterns. The findings reveal recurring violations, including the employment of foreign workers without approved RPTKA, mismatches between job positions and work locations, failure to implement mandatory skill transfer programs, non-payment of the Compensation Fund (DKPTKA), and inconsistencies in immigration permits. These issues stem from weak inter-agency coordination, low corporate compliance awareness, and the absence of measurable standards for evaluating skill transfer.  The study recommends risk-based joint inspections, integration of RPTKA data with workforce realization, measurable skill transfer standards, graduated administrative sanctions, and strengthened compliance campaigns to ensure legal certainty and protect local workers.